Perlindungan Hukum Terhadap Hak Konpensasi Pemutusan Hubungan Kerja Menggunakan Aset Direksi (Studi Kasus Akta Perdamaian Nomor 1404/PDT.G/2021/PN.TNG) - Solihin (Jurnal Ilmu Pendidikan dan Sosial, 2023)
Whereas in labor relations there are often obstacles, such as termination of employment. For workers, this study uses a normative juridical approach, in the form of a case approach by conducting a study of related cases, which have become court decisions that have permanent legal force. The case study in this research is related to the Deed of Peace Number 1404/Pdt.G/2021/PN.Tng. This study aims to determine the legal protection of compensation rights for termination of employment using directors' assets and the constraints faced. The results of this study explain that termination of employment for workers at PT. Aemka Putra Satria towards 6 (six) workers who have worked for 15 years. Due to the company's incompetence, and there are no company assets that can be used to pay for workers' rights, the good faith and moral responsibility of the directors, a Debt Payment Agreement (Severance Payment) was made on November 28, 2019. The value of workers' rights is Rp. 900,000.000 (nine hundred million rupiah). Will be paid by selling the directors' personal assets in the form of land with a Certificate of Ownership No. 07578 which is located in Gang Ronyok Binong Tangerang with an area of ​​775 m2 with estimated sales of Rp. 1,550,000,000. Because there was no realization of the agreement, the workers through their attorneys filed a lawsuit for default at the Tangerang District Court on December 23, 2021. Based on the results of mediation, a Peace Agreement was produced to be determined in the settlement of peace (acta van dading). Based on the Deed of Peace Number 1404/Pdt.G/2021/PN.Tng, the Panel of Judges at the Tangerang District Court determined the peace agreement in the Establishment of the Deed of Peace, in which the parties must comply with the agreement of the parties that had been approved.